Ultrasonic measurement of lubricant film thickness in sliding Bearings with overlapped echoes. (August 2015) - Zhang, Kai; Meng, Qingfeng; Geng, Tao; Wang, Nan
Abstract: The lubricant film thickness in sliding bearings with a thin liner have previously been immeasurable due to the overlapping of ultrasonic signals making the use of the ultrasonic spring model impossible. In this paper, we firstly modeled the overlapped echoes in terms of superimposed Gaussian echoes corrupted by noise and used the EM algorithms to extract the interested echo. Then the extracted echo was used to obtain the lubricant film thickness by an ultrasonic spring model. A high precision calibrated rig which could form a series of known film thicknesses was set up and the performance of the method was shown to work well. Highlights: We measure the film thickness in four-layer structure by an ultrasonic spring model. We use the EM algorithms to separate the overlapped ultrasonic echoes. We build a high-precision calibrated rig and the method is shown to work well. The proposed method improves the capability of the ultrasonic spring model.